Characterization of the metastable Cu-Fe nanoparticles prepared by the mechanical alloying route - Mahsa Barzegar Vishlaghi; Abolghasem Ataei (Journal of Ultrafine Grained and Nanostructured Materials, 2014)
Although Cu and Fe are immiscible under equilibrium conditions, they can form supersaturated solid solutions by mechanical alloying. In this paper, nano-structured of the metastable Cu-Fe phase containing 10, 15, 20 and 25% wt Fe were synthesized by intensive ball milling for 15h, in order to achieve a solid solution of Fe in Cu. The phase composition, dissolution of the Fe atoms into the Cu matrix, and the morphology of the milling products were studied by X-ray Diffraction (XRD), Energy Dispersive Spectrometer (EDS), and Field Emission Scanning Electron Microscope (FESEM) techniques, respectively. The mean crystallite size of the milled samples was determined by XRD peak broadening using the Williamson-Hall approximation. The XRD analysis results showed that the solid solubility of the Fe in the Cu was extended to 20%wt after milling for 15 h, and a homogeneous solid solution of Cu80Fe20 with a mean crystallite size of 19nm was obtained. The mean crystallite size decreased with increasing milling time and it was more evident in the initial stage of the milling. The Cu lattice parameter increased by dissolving the Fe into the Cu matrix probably due to the magneto-volume effect in the Cu-Fe alloys. The FESEM observations showed that the milling products were agglomerates consisting of uniform particles. The Vibrating Sample Magnetometer (VSM) results showed that the Cu80Fe20 powder has soft magnetic properties.